THE URGENCY OF CULTURAL REVITALIZATION IN THE INDONESIA-MALAYSIA BORDER REGION - Ersa Tri Fitriasari (Bajang Institute, 2022)
This study focuses on the cultural revitalization aspect as an urgent matter in the Indonesia-Malaysia border region, SajinganBesar Sub-district, Sambas Regency. The results of this study can be summarized that the main problem of cultural development in the border region is not only caused by globalization but also concerns on the condition of cultural resilience of the border communities themselves who have experienced stagnation which is from the conditions that are completely and inevitably marginal of Globalization, then it must be anticipated with cultural development that is characterized by the reinforcement of identity and local wisdom of the border community which is used as the basis for arranging strategies in preserving and developing culture. This study used a qualitative approach that was carried out by survey data, observation, analysis and FGD (Forum Group Discussion). This method is very effective for something that is urgent and important and will provide an increase in the welfare of the community whose life is generally less prosperous. Moreover, geopolitically, the cultural revitalization will further ensure the realization of the revitalization policy of the culture of the Indonesian Archipelago in the border region which can create nationalism, and maintain the border region from foreign infiltration as well as become a space for conflict resolution to create peace between countries. This study focuses on the cultural revitalization aspect as an urgent matter in the Indonesia-Malaysia border region, Sajingan Besar Sub-district, Sambas Regency. The results of this study can be summarized that the main problem of cultural development in the border region is not only caused by globalization but also concerns on the condition of cultural resilience of the border communities themselves who have experienced stagnation which is from the conditions that are completely and inevitably marginal of Globalization, then it must be anticipated with cultural development that is characterized by the reinforcement of identity and local wisdom of the border community which is used as the basis for arranging strategies in preserving and developing culture. This study used a qualitative approach that was carried out by survey data, observation, analysis and FGD (Forum Group Discussion). This method is very effective for something that is urgent and important and will provide an increase in the welfare of the community whose life is generally less prosperous. Moreover, geopolitically, the cultural revitalization will further ensure the realization of the revitalization policy of the culture of the Indonesian Archipelago in the border region which can create nationalism, and maintain the border region from foreign infiltration as well as become a space for conflict resolution to create peace between countries.